2019
DOI: 10.3390/geosciences9090374
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Glacier Surface Velocities and Outlet Areas on James Ross Island, Northern Antarctic Peninsula

Abstract: The northern Antarctic Peninsula was affected by a significant warming over the secondhalf of the 20th century and the collapse of several ice shelves. Local climate conditions on James RossIsland on the northeastern coast can differ strongly from the main part of the Antarctic Peninsula.This paper reports the spatial and temporal variability of glacier surface velocities and the area oftheir outlets throughout James Ross Island, and evaluates potential relationships with atmosphericand oceanic conditions. Vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Details to the processing can be found in Seehaus et al [31]. Furthermore, unreliable velocity estimates, mostly near to the cliff where the standard deviation in a 21 × 21 pixel moving window is larger than 0.5 m d −1 , were excluded [23]. Velocity maps of Gourdon Glacier are available for the period August 2014 until April 2018 (Table A1) at Pangaea doi:10.1594/PANGAEA.907062.…”
Section: Estimation Of Surface Velocities From Satellite Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Details to the processing can be found in Seehaus et al [31]. Furthermore, unreliable velocity estimates, mostly near to the cliff where the standard deviation in a 21 × 21 pixel moving window is larger than 0.5 m d −1 , were excluded [23]. Velocity maps of Gourdon Glacier are available for the period August 2014 until April 2018 (Table A1) at Pangaea doi:10.1594/PANGAEA.907062.…”
Section: Estimation Of Surface Velocities From Satellite Datamentioning
confidence: 99%
“…Accumulated SMB data for the year 2017 on Gourdon Glacier were taken from the nearest grid cells in the MAR regional climate model in the version 3.9 with a spatial resolution of 7.5 km [21,22]. In Lippl et al [23], the suitability of MAR regarding the differences between the lower lying outlet glaciers and the higher elevated plateau on JRI were evaluated by in situ measurements for different climate variables. Data revealed that for temperature, surface pressure and relative humidity, MAR is able to reflect the temporal variability at the outlet glaciers with a reasonable constant bias.…”
Section: Ice Thickness Interpolation and Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations